Association of Circulating Adipokines With Echocardiographic Measures of Cardiac Structure and Function in a Community‐Based Cohort. Issue 13 (3rd July 2018) - von Jeinsen, Beatrice; Short, Meghan I.; Xanthakis, Vanessa; Carneiro, Herman; Cheng, Susan; Mitchell, Gary F.; Vasan, Ramachandran S.
Abstract : Background: Adipokines mediate cardiometabolic risk associated with obesity but their role in the pathogenesis of obesity‐associated heart failure remains uncertain. We investigated the associations between circulating adipokine concentrations and echocardiographic measures in a community‐based sample. Methods and Results: We evaluated 3514 Framingham Heart Study participants (mean age 40 years, 53.8% women) who underwent routine echocardiography and had select circulating adipokines measured, ie, leptin, soluble leptin receptor, fatty acid–binding protein 4, retinol‐binding protein 4, fetuin‐A, and adiponectin. We used multivariable linear regression, adjusting for known correlates (including weight), to relate adipokine concentrations (independent variables) to the following echocardiographic measures (dependent variables): left ventricular mass index, left atrial diameter in end systole, fractional shortening, and E/e′. In multivariable‐adjusted analysis, left ventricular mass index was inversely related to circulating leptin and fatty acid–binding protein 4 concentrations but positively related to retinol‐binding protein 4 and leptin receptor levels ( P ≤0.002 for all). Left atrial end‐systolic dimension was inversely related to leptin but positively related to retinol‐binding protein 4 concentrations ( P ≤0.0001). E/e′ was inversely related to leptin receptor levels ( P =0.0002). We observed effect modification by body weight for select associations (leptin receptor and fatty acid–binding protein 4 with left ventricular mass index, and leptin with left atrial diameter in end systole; P <0.05 for interactions). Fractional shortening was not associated with any of the adipokines. No echocardiographic trait was associated with fetuin‐A or adiponectin concentrations. Conclusions: In our cross‐sectional study of a large, young to middle‐aged, relatively healthy community‐based sample, key indices of subclinical cardiac remodeling were associated with higher or lower circulating concentrations of prohypertrophic and antihypertrophic adipokines in a context‐specific manner. These observations may offer insights into the pathogenesis of the cardiomyopathy of obesity.